TATA KELOLA PERUSAHAAN DAN PENGUNGKAPAN RISIKO: BUKTI DARI PARA PENGADOPSI PELAPORAN TERINTEGRASI (Studi empiris pada perusahaan non-keuangan yang terdaftar di Bursa Efek Indonesia tahun 2024) - Rhino Ariel Septyanto; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2026)
This study was designed to explore the extent to which corporate governance quality moderates or influences the breadth and depth of risk information disclosure in integrated reports among Indonesian non-financial issuers. The variables utilized in this research are Board of Commissioner Size (UDK), Board of Commissioner Gender Diversity (KGDK), Board of Commissioner Independency (IDK), and Board of Commissioner Meeting Frequency (FRDK) as independent variables, the Risk Disclosure Indeks (IPR) as the dependent variable, as well as Profitability (PROF), Company Size (UkP), Company Age (UmP), High-Technology Industry (ITT), Environmental Sensitivity (SL), and Audit Committee Size (UKA) as control variables.            This study observed the population of non-financial companies listed on the Indonesia Stock Exchange (IDX) during 2024. Through the application of purposive sampling techniques, 153 observations relevant to the research criteria were obtained. Furthermore, hypothesis verification was carried out using multiple linear regression analysis with computational support from SPSS (Statistical Product and Service Solutions) software.            Research findings indicate that the size of the Board of Commissioners and gender diversity on the Board of Commissioners have a significant negative impact on the extent of risk disclosure in integrated reports. Meanwhile, Board of Commissioner Independency and Board of Commissioner Meeting Frequency were found to have no significant impact on the extent of risk disclosre in integrated reports.